2018
DOI: 10.1016/j.appet.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Why aren't you stopping now?!’ Exploring accounts of white women breastfeeding beyond six months in the East of England

Abstract: Breastfeeding infants for a period of two years is endorsed by international health agencies such as the World Health Organisation. However, discourses of breastfeeding in a British context are complex and contradictory, juxtaposing representations of breastfeeding as healthy and a moral obligation for mothers with views of the act as unseemly and an expectation that nursing women practice 'socially sensitive lactation' especially in public spaces. Sustained breastfeeding rates in the UK are poor and most Brit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 54 publications
0
43
0
6
Order By: Relevance
“…The effect of breastfeeding was also dose-dependent, with longer duration and exclusivity increasing its effects 32 . The WHO recommended to further breastfed infants up to two years 33 , as children's health and development continued to benefit from the provision of breast milk 34 . To our knowledge, no other study previously described this association and it might entail an important mechanism to explain the positive effects of breastfeeding on the energy metabolism [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of breastfeeding was also dose-dependent, with longer duration and exclusivity increasing its effects 32 . The WHO recommended to further breastfed infants up to two years 33 , as children's health and development continued to benefit from the provision of breast milk 34 . To our knowledge, no other study previously described this association and it might entail an important mechanism to explain the positive effects of breastfeeding on the energy metabolism [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the mean age to terminate any breastfeeding was 18.3 months, which is in agreement with previous research suggesting that people tend to underestimate the recommended total time for any breastfeeding (Fairbrother & Stanger‐Ross, ; Rempel & Rempel, ). Although not explored explicitly in this study, social disapproval of breastfeeding older infants and toddlers has been well documented (Cockerham‐Colas, Geer, Benker, & Joseph, ; Dowling & Brown, ; Newman & Williamson, ; Rempel, ; Stearns, ). Low awareness and potentially low acceptance of the recommendation to continue breastfeeding for toddlers may be contributing to reduced adherence to the recommendation for continued breastfeeding for 2 years and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Although not explored explicitly in this study, social disapproval of breastfeeding older infants and toddlers has been well documented (Cockerham-Colas, Geer, Benker, & Joseph, 2012;Dowling & Brown, 2013;Newman & Williamson, 2018;Rempel, 2004;Stearns, 2011).…”
Section: Iycf Knowledge Deficitsmentioning
confidence: 99%
“…These studies also raise issues around language, disputing the terms 'extended' or 'long term' breastfeeding in toddlerhood due to the connotations it implies. A recent qualitative exploration of eight white women breastfeeding beyond six months offer insights into issues such as stigma, breastfeeding etiquette, media representations and the need for supportive family and friends (Newman and Williamson 2018). It's concluded that HV's could be better trained and educated on benefits of continued breastfeeding, however, what is unclear is the mothers' experiences of these professionals.…”
Section: Understanding Experiences Of Breastfeedingmentioning
confidence: 99%